Benefits of Glulam Timber Roof Structure for Airport Passenger Terminal Buildings - Lakshmanan, Ravi (PREPARE@u® | IEI Conferences, 2021)
Airport passenger terminals vary in shape, form and interior design. Most of the terminals’ roof structure at the uppermost building level is a steel structure with a curved shape and false ceiling/cladding to give a pleasant view. Very few buildings have a concrete roof at this level. Nowadays, designers look for green building materials such as timber instead of steel, as wood has many advantages. Architects understand the importance of architectural features of the passenger terminals while conceptualizing the design to create an attraction with an element of uniqueness. An airport in the Philippines utilized Glulam as a roof structure material for the passenger terminal building and achieved its design intent matching local culture. The terminal received appreciation from all the stakeholders and proved the rationale for choosing this material. It is also essential to be aware of the limitations of glulam material, and adequate care is taken during planning, implementation and maintenance of the asset. Selection of suitable materials, construction methodology and project management ensures delivery of the projects in timeAirport passenger terminals vary in shape, form and interior design. Most of the terminals’ roof structure at the uppermost building level is a steel structure with a curved shape and false ceiling/cladding to give a pleasant view. Very few buildings have a concrete roof at this level. Nowadays, designers look for green building materials such as timber instead of steel, as wood has many advantages. Architects understand the importance of architectural features of the passenger terminals while conceptualizing the design to create an attraction with an element of uniqueness. An airport in the Philippines utilized Glulam as a roof structure material for the passenger terminal building and achieved its design intent matching local culture. The terminal received appreciation from all the stakeholders and proved the rationale for choosing this material. It is also essential to be aware of the limitations of glulam material, and adequate care is taken during planning, implementation and maintenance of the asset. Selection of suitable materials, construction methodology and project management ensures delivery of the projects in time.